Synthesis, characterization and antimicrobial evaluation of 1-((5,3-diaryl)-4,5-dihydro-1H-pyrazol-1-yl)propan-1-one - Sid, Assia; Ziani, Nouara; Demmen-Debbih, Ouafa; Mokhtari, Mahieddine; Lamara, Kaddour (European Journal of Chemistry, 2013)
1-((5,3-Diaryl)-4,5-dihydro-1H-pyrazol-1-yl)propan-1-one, 6-10, have been synthesized by the reaction of chalcone derivatives, 1-5, with hydrazine hydrate in hot propanoic acid solution. All these compounds were characterized by different spectroscopic techniques (FT-IR, 1H and 13C NMR) and elemental analyses. All the synthesized products were evaluated for antimicrobial activity. All the compounds exhibited significant to moderate antimicrobial activity.